Humanism Approach in Children Education: A Look Into Humane Perspective Of Teaching English To Children - Wahyu Indah Mala Rohmana; Renata Kenanga Rinda (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Recently language teaching has been influenced by number of approaches. In case of teaching children, there are many approaches which can be implemented according to the children needs. This paper is a library research which attempts to explain teaching English for children viewed from humanism theory. The humanism theory or approach is very crucial in teaching children. Humanism theory sees a human connection is vital matter to young learners education and makes them to self-actualize in their learning process. It builds emotional relationship between teachers and students and student-centered teaching. In conclusion, whatever methodology adopted by the teacher to suit the needs of children, a teacher with a humanistic approach will make them learn to remember, to understand, to think and to learn.